Analisis Pengelolaan Dana Desa - Saiful Amrin (IPM2KPE, 2022)
This study aims to determine the management of village funds in Balukhering Village, Lewolema District, East Flores Regency. This research method is descriptive qualitative. Data were collected by using in-depth interviews, observation and documentation techniques. The data collected was then analyzed using a comparative descriptive method, by collecting, compiling, interpreting and analyzing Village Fund management data based on the Regulation of the Minister of Home Affairs Number 113 of 2014 concerning Village Financial Management in Balukhering Village. The results showed that there were 4 (four) indicators that were not appropriate, namely spending before the Village Budget was determined, village expenditures including binding personnel expenditures and office operations. SPP can be done before the goods or services are received and the activity implementer does not make a statement of expenditure responsibility. The overall administration implementation has been going well and is in accordance with the Minister of Home Affairs Regulation Number 113 of 2014 concerning Village Financial Management, but has a delay in reporting each month to the village head. The reporting and accountability stage is in accordance with Permendagri Number 113 of 2014 concerning village financial management . The conclusions, planning, administration, reporting and accountability of Balukhering village funds have been carried out according to the law, while the implementation stage has not gone well. Keywords: Village Fund, Management